Wind cooling during a self-paced cycling time trial - Teunissen, L.; de Haan, A.; de Koning, J.; Daanen, H. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Wind has been shown to be an effective cooling method during fixed-paced exercise in the heat, decreasing thermal strain and increasing time to fatigue. However, it has been scarcely investigated in what way these observations translate to self-paced performance. So the aim of this experiment was to study how wind cooling affects thermal strain, thermal perception, pacing and performance during a 15 km cycling time trial in strenuous climatic conditions. Methods: Ten male subjects performed two 15 km cycling time trials in a climatic chamber set at 28°C and 80% relative humidity. In one of the time trials, a wind tunnel unexpectedly provided head wind (~4 m/s) during the middle part of the race (3-12 km). Conditions (control: CO and wind: WI) were offered in balanced order with at least two days in between. Measurements included rectal temperature (Tre), average skin temperature (Tsk), heart rate (HR), fluid loss, rate of perceived exertion (RPE, each km), thermal sensation (TS, each 5 km), thermal comfort (TC, each 5 km), power output (PO) and finish time. Results: WBGT was similar at the start of both trials (26.5±0.08°C) and dropped when wind was applied to 26.0±0.04°C. Overall, subjects had a higher PO in the WItrial than the CO-trial (246±11 vs. 235±9 W), leading to a 75±24 s faster finish time. Per kilometer, PO differences between conditions were detected from km 4 to 14. These differences were largest in km 4 and km 11-14 (14-19 W). Tre was similar for CO and WI during each kilometer of the trial. However, wind application induced a clear difference in Tsk from km 4 to 15, being maximally 1.98±0.16°C lower for WI than for CO (km 12). This was reflected in lower RPE values during km 5-13 and improved TS and TC values at the 5 and 10 km mark of the WI-trial. HR was lower during km 10-15 of WI (about 4-6 bpm). No differences in fluid loss and fluid ingestion were observed. Discussion: Despite a nearly similar WBGT value, wind application during self-paced exercise in a warm humid environment substantially reduced thermal strain and improved performance. Wind instantly induced a decrease in Tsk, attenuation of RPE and increase in power output. The higher PO was maintained throughout the wind interval at similar or lower Tre and HR values than during the CO-trial, with subjects feeling less exerted, cooler and more comfortable. This may have led to the slightly increased power profile in the last 5 km of the WI-trial (even though wind stopped blowing at 12 km), while PO in the CO-trial was not increased until the final kilometer. In conclusion, wind is an effective tool to provide immediate and constant benefits in thermal perception and performance during self-paced exercise in the heat.